Detecting bubbles in world aluminum prices: Evidence from GSADF test - Menglin Ni; Xiaoying Wang (Journal of Business Economics and Management, 2024)
The aim of this research is to assess the existence of multiple bubbles in the global aluminum market by employing the Generalized Supremum Augmented Dickey-Fuller (GSADF) methodology. This method offers practical time series analysis tools for identifying periods of rapid price escalation, followed by subsequent collapses. Findings indicate the identification of six explosive bubbles occurring between January 1980 and March 2023, during which the aluminum price strayed from its underlying fundamental value. Additionally, this finding is consistent with the asset pricing model, which generally considers both fundamental and bubble components. Based on the empirical results, the aluminum price bubbles are positively influenced by the copper price, GDP, the U. S dollar index, industrialization of China, China’s urbanization rate, whereas the global aluminum production, oil price, and base metal price index have a negative explanatory effect on the aluminum price bubbles. To effectively stabilize the international aluminum price, policymakers are suggested to be vigilant in identifying bubble episodes and monitoring their progression. Additionally, regulatory authorities should implement measures to curb excessive speculative activity during periods of extreme market volatility, thereby mitigating excessive price fluctuations and the formation of aluminum bubbles.